The correlation of visual inspection, Pap-smear and immunocytochemistry of human papilloma virus in detection of cervical cytology - Khemka, Anuradha; Jajoo, Shubhada (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Carcinogenicity presents as a major challenge to scientists and society.. Cervical cancer ranks fifth in the world and is the second cause of death in developing countries like India and China. The rate of death due to cervical cancer is greatest in India. At any time women are at risk of harboring HPV infection, which has been seen to cause cervical cancer. Clinical judgment should be used in spite of all high quality modalities available for screening and diagnosis, as initiated by WHO (World health organization) the Down Staging of cervical cancer, VIA, VILI, Pap smear introduced by George Papanicolaou in 1940s , HPV testing by Immunocytochemistry (ICC) and HPV DNA , Colposcopy , are other modalities to screen cervix. The study aims to evaluate the correlation between Pap smear, visual inspection and Immunocytochemistry of Human papilloma virus (HPV). Methods: All 100 consecutive women were subjected to visual inspection of cervix, Pap smear and immunocytochemistry of HPV. Pap smear was done by conventional method. Results: it was seen that out 100 consecutive cervico-vaginal, ears for Pap and Immunocytochemistry, only 33 were abnormal, 24 were ASCUS, 6 were LSIL, 2 were HSIL, 1 was SCC and 67 were NILM out of which 3 were reactive for ICC. And all 33 were reactive for ICC. Conclusions: The p16 immunostaining performed on conventional smears can become alternative or addition to l HPV DNA tests. The Bethesda System (TBS) 2001 for reporting cervical cytology diagnosis is of high value in detecting abnormal cervical cytology. It is further concluded that the ancillary screening for HPV in NILM category seems to be not advisable as percentage of detection of HPV in this category is low.